The Quotidian, Small and Incomplete: WWII and the Indifference of Things - Figenschau, Ingar (Archaeological Society of Finland, 2019)
Source at http://www.sarks.fi/fa/faxxxvi.html . This article examines how things contribute to an expanded and different understanding of contexts that are usually reserved for historical inquiry. To show this, the article illustrates how archaeological investigations of World War II prison camps connected to the German defensive Lyngen Line in northern Norway have uncovered aspects that are absent or unavailable in historical sources. Accordingly, it is argued that archaeology of the recent past is not the ‘handmaiden to history’. How so? First, archaeological excavations and post-field work enable a unique material proximity and awareness. Secondly, fragmented artefacts offer new and different insights that do not rely on historical tropes. In conclusion, things are time witnesses that are not influenced by historical hindsight: they can present fragmented, unpleasant, personal and intimate aspects that are too trivial to be included in the grand narratives, but as archaeological investigations demonstrate, were fundamental to the everyday life of war.